Improving Guidelines for the Plant Available Nitrogen Value of Biosolids from Wastewater Treatment - Rigby, Hannah; Pritchard, Deborah; Collins, David; Walton, K.; Allen, D.; Penney, N. (DEStech Publications, Inc., 2010)
It is important to accurately quantify the amount of plant available nitrogen (PAN) in land applied biosolids to achievemaximum crop production, yet reduce the risk of pollution through nitrate leaching and gaseous losses following excess applications or incorrect management. For this reason, biosolids application rates are frequently determined by the PAN content based on the mineralisable portion of the organic nitrogen (N). The findings of this field experiment, conducted in an acidic sand under aMediterranean-type climate inWestern Australia, demonstrate that the PAN of biosolids relative to an inorganic source of N is dependent on the treatment method of the biosolids, with greater PAN from lime amended biosolids (65.1%) and alum-dosed biosolids (63.4%) in comparison to dewatered biosolids cake (39.4%). The amount of organic N that becomes available in the first season may be 2–3 times greater than the current estimate of 20% used to calculate application rates inWestern Australia. It is suggested that current biosolids guidelines in Australia require further investigation to maximise crop yield andeconomic benefits of biosolids application and prevent pollution from leaching of excess mineral N.